ANALISIS TEORI FRAUD PENTAGON S.C.O.R.E METHOD DALAM MENDETEKSI FRAUD PADA LAPORAN KEUANGAN PERUSAHAAN - Angelina, Claudia; Natalis Christian (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research’s aim to analyze factors affect fraud of the company's financial statements on the pentagon's fraud theory S.C.O.R.E Method in order to prevent fraud of financial statements occur. In the theory of S.C.O.R.E Method consists of independent variables in the form of Stimulus, Capability, Opportunity, Rationalization, and Ego. Financial statement detection tool used in this study is F-Score. Sample Detection of fraud in financial statements of Go Public companies which not operate in the property, real estate, finance and construction fields registered in IDX with 2014-2020 period, as rupiah currency. Quantitative data sources are used in detecting fraud against a company's financial statements and are tested using the SPSS version 25 application and Eviews version 10. The results of the study resulted in data that Stimulus, Capabily, and Ego variables had a positive significant on financial statement fraud. Opportunity variable has a znegative significant influence on financial statement fraud. Variable that not significant influence on financial statement fraud is Rationalization variable.